2019
DOI: 10.1063/1.5127768
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of hafnium optical and near-IR kinetic inductance detectors

Abstract: We report on the design and performance of Microwave Kinetic Inductance Detectors (MKIDs) sensitive to single photons in the optical to near-infrared range using hafnium as the sensor material. Our test device had a superconducting transition temperature of 395 mK and a room temperature normal state resistivity of 97 µΩ cm with an RRR = 1.6. Resonators on the device displayed internal quality factors of around 200 000. Similar to the analysis of MKIDs made from other highly resistive superconductors, we find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…It is striking that most substrate-based MKIDs with a high enough R SN are all limited to R ≈ 10 − 20 3,[12][13][14]16,17 . Here we conclusively show that in Al MKIDs on substrate R is limited by hot phonon loss.…”
Section: B Towards a Fano-limited Resolving Powermentioning
confidence: 99%
See 1 more Smart Citation
“…It is striking that most substrate-based MKIDs with a high enough R SN are all limited to R ≈ 10 − 20 3,[12][13][14]16,17 . Here we conclusively show that in Al MKIDs on substrate R is limited by hot phonon loss.…”
Section: B Towards a Fano-limited Resolving Powermentioning
confidence: 99%
“…For PtSi, with T c = 0.9 K, R = 5.8 − 8.1 at wavelengths of 1310-808 nm (a best δE = 0.16 eV) [13]. For Hf with T c = 0.4 K, R = 6.8 − 9.4 (best δE = 0.14 eV) for the same wavelengths [14]. In devices optimized for photon-number resolution using TiN/Ti/TiN trilayers R = 3.6 at 1550 nm [15].…”
Section: Introductionmentioning
confidence: 97%
“…The error bars represents the standard deviation over the wafer. The data point from N. Zobrist et al [10] is also shown for comparison even though a different sputter system was used. The superconducting transition temperature (Bottom Left) and calculated kinetic inductance using equation 1 (Bottom Right) for the same films are also given.…”
Section: Hafnium Film Depositionmentioning
confidence: 99%
“…A photon's energy, then, can be extracted from the overall size of the signal. These types of MKIDs are called single photon counting, and examples of them include lumped element optical to near-IR detectors, [2][3][4][5][6] X-ray thermal kinetic inductance detectors, [7][8][9][10] and position dependent strip detectors. 11,12 The properties of an MKID are encoded in the forward scattering matrix element, S 21 , of the resonator.…”
Section: Introductionmentioning
confidence: 99%